Emerging value capture innovative urban rail funding and financing: A framework - Kumar Jillella, S.; Sitharam, T.; Matan, A.; Newman, Peter (2016)
© 2017 by IGI Global. All rights reserved. Urban rail transit is emerging around the world as a catalyzing developmental solution to enable 21st century sustainable cities. However, these transit systems are capital intensive and cities worldwide are seeking innovative funding and financing mechanisms. Recently, land based value capture (VC) mechanisms have emerged as a pioneering solution to fund urban rail projects. This chapter introduces the VC concept and provides global best practice. The chapter aims to help enhance the understanding and rationale behind VC approaches through assessing the transit impacted accessibility value proposition and various VC mechanisms to capture the value created. A six-step Strategic Value Capture (SVC) framework is proposed which offers a step-by-step guidance to help define the VC based urban rail transit funding and financing processes from VC planning to VC operations.